2012
DOI: 10.5005/jp-journals-10016-1045
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Some Genetic Factors Controlling Spermatogenesis in Egyptian Patients with Male Infertility

Abstract: Men with severe infertility suffer a high risk of Y chromosome deletion, hence screening for these cases is recommended prior to treatment with assisted reproduction. Our study aimed to investigate and detect the azoospermia factor (AZF) region deletion, rearrangement and deleted azoospermia (DAZ) gene copy number variations in Egyptian azoospermic infertile men. This was tested on 54 Egyptian nonobstructive azoospermic (NOA) infertile men, with age ranged from 21 to 45 years (mean: 31.4 ± 6.1 years), by STS ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 24 publications
(22 reference statements)
6
3
1
Order By: Relevance
“…In our patients, we found that the Klinefelter syndrome 47; XXY was the most common in azoospermic men (9.25 %) than in oligospermic severe men (1.55 %). In consistence with other studies [ 21 , 22 ], the mosaic forms of Klinefelter syndrome was found only in two azoospermic patients. Most men with KS are azoospermic and their ability to conceive remained too low [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our patients, we found that the Klinefelter syndrome 47; XXY was the most common in azoospermic men (9.25 %) than in oligospermic severe men (1.55 %). In consistence with other studies [ 21 , 22 ], the mosaic forms of Klinefelter syndrome was found only in two azoospermic patients. Most men with KS are azoospermic and their ability to conceive remained too low [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…Men with this syndrome can have phenotype similar to those with Klinefelter’s syndrome with normal male external genitalia, but they are sterile [ 29 ]. Studies have shown that the frequency of XX males among azoospermic varies between 0.6 % [ 30 ] and 3.7 % [ 21 , 22 ]. In our study, the frequency of this chromosomal abnormality was 1.36 %.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the AZFc deletion frequency was represents 68.8% (31 /45) followed by the AZFbc region 15.5% (7/ 45), AZFb 8.8% (4/ 45) and AZFa 6.6% (3/ 45) illustrated in (Table 4,). These results which were similar to other studies [8,9,30,55] . On the other hand, Mohamed et al [20] found that the AZFbc combination regions was the most frequently deleted regions (5, 71.4%) followed by AZFc (2, 26.8%) with no separate microdeletions in either AZFb and/or AZFa in their Kuwaiti infertile males from Kuwait.…”
Section: Discussionsupporting
confidence: 93%
“…It represents 66% (2640/) of AZF deletions in NOA and 100% (55/) in SOZ. This result is comparable to the previously reported range (46.687.1%-) for AZFc deletion in several studies from different populations [9,24,25,51,53,55,57,65] . In contrast to these studiesHowever, Mafra et al [28] reported no AZFc deletions in their Brazilian NOA men.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation